2020
DOI: 10.1016/j.nmni.2020.100746
|View full text |Cite
|
Sign up to set email alerts
|

The current situation of COVID-19 in Sudan

Abstract: The outbreak of coronavirus disease 2019 (COVID-19) caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is a global public health concern with rapid growth in the number of patients with significant mortality rates. The first case in Sudan was reported on 13 March 2020, and up to 3 July 2020 there are 9894 confirmed cases and 616 deaths. The case fatality rate was 6.23%. There is variation in case fatality rate (CFR), which in some cities (like Khartoum) was low (3.8%), but in others (like N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
39
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 15 publications
1
39
1
Order By: Relevance
“…preventive measures by the government. 4 On the other hand, the mortality rate in our study was markedly higher than that reported in different studies across the globe: Italy (0.007%, 0.005%), 15 India (2 to 3%), 25 the United States of America (6%), 13 and France (22.8%). 26 Many explanations have been proposed for the considerable variation in the mortality rate in different parts of the world.…”
contrasting
confidence: 70%
See 4 more Smart Citations
“…preventive measures by the government. 4 On the other hand, the mortality rate in our study was markedly higher than that reported in different studies across the globe: Italy (0.007%, 0.005%), 15 India (2 to 3%), 25 the United States of America (6%), 13 and France (22.8%). 26 Many explanations have been proposed for the considerable variation in the mortality rate in different parts of the world.…”
contrasting
confidence: 70%
“…24 This study documented a general mortality rate of 37.5%, which is higher than the general case fatality rate (6.23%) that was recently reported for Sudan. 4 However, higher mortality rates were also found in North Darfur (31.7%) and Central Darfur (60%) in Sudan. 4 This extreme variation in mortality in Sudan might be related to the lack of hospitals, under-reporting the actual number of cases due to a lack of testing facilities, and could also be attributed to the partial success of the implemented…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations